THE ROLE OF PARENTS IN ISLAMIC EDUCATION IN THE MILLENNIAL ERA IN GERENENG VILLAGE, EAST SAKRA DISTRICT - Mardiani (Indonesian Journal of Education and Science, 2024)
This study explores the role of parents in providing Islamic education to children in Gereneng Village during the millennial era. With the increasing impact of digital media and economic pressures, traditional family-centered religious education faces unique challenges. The research, conducted through interviews and observations, reveals the diverse levels of parental involvement, influenced by both economic demands and technology usage among children. Findings indicate that while some parents struggle to manage their children’s digital engagement, others emphasize early Islamic education and community participation. This study concludes that integrating traditional Islamic values with modern educational demands is essential to foster well-rounded character development in the younger generation. Practical implications suggest that family-based educational approaches tailored to modern challenges can enhance the effectiveness of Islamic upbringing in rural settings. The study provides insights into the adaptability required in rural communities to sustain Islamic education in an evolving socio-technological landscape.